Problems of Programming the Excavator Work Motions - Płonecki, L. (Engineering Transactions, 1997)
The present paper discusses the problems connected with programming the cutting tool trajectory in the automated earth mover, exemplified by the single-bucket hydraulic excavator. They are related mainly to the tool path planning within the configuration and Cartesian coordinates, and to trajectory parametrization in time. Furthermore, the author presented the examples of the trajectory design for the hydraulic excavator, and the results of experiments performed at the laboratory stand with K-111 excavator fixture.